Exploring Knowledge and Attitudes towards Community-Based Tourism and Homestays in Nepal - K.C. , Rabindra; Shrestha, Nirjal; Tamang, Rajan; Thapa, Rajesh; Sherpa, Ridorchi (International Journal of Atharva, 2025)
Background: Community-based tourism (CBT) is vital for sustainable rural development in Nepal, yet public awareness and attitudes toward it are not well understood.Objectives: This study assessed Nepalese residents' awareness of CBT, their attitudes toward its cultural, environmental, and economic impacts, and their future engagement intentions.Methods: A cross-sectional survey was conducted with 213 participants from key stakeholder groups, including homestay operators, local residents, officials, and tourists, using convenience sampling.Findings: Most respondents (65.2%) could name a homestay destination and recognized CBT's benefits: cultural preservation (73.2% agreement), environmental sustainability (70.4%), and local economic improvement (75.6% agreement on revenue retention). Most (76.0%) preferred homestays for future travel.Conclusion: There is strong awareness and positive perception of CBT's benefits in Nepal, indicating its potential for sustainable tourism.Implication: Findings support enhancing CBT through government training, academic integration, and policy prioritization to boost rural development.